Improving Speaking Abilty by Using Turn Taking Strategy (a collaborative classroom action research to the second year students of SMAN 1 Nisam) - Dewi Kumala Sari; Rasyimah (Medan Resource Center, 2021)
Language is the ability of human to communicate with other humans using sign, such as word and movements with the aim of develomping their potential. The research was conducted at SMAN 1 Nisam, North Aceh District. The purpose of the research is to know whether Turn Taking Strategy can improve students’ ability in speaking and to know the class atmospheres when the teacher teaches speaking by using Turn Taking Strategy. The design applied in this research is a qualitative approach and the type is an action research collaborative. This research will do in several phase: 1) preliminary study, 2) planning and action, 3) implementation of the action, 4) observation, and 5) data and reflection. The result showed, From the results of speaking test, there was an improvement of students’ speaking ability. It could be seen from the results of the posttest. There was an improvement in students’ interest in teaching learning process. It was proven they were more active and attention in instructional process. Students were more enthusiastic in English lesson. They did the task and assignment seriously